Structural characterization of a polysaccharide from bamboo (Phyllostachys edulis) shoot and its prevention effect on colitis mouse. (1st September 2022) - Li, Qi; Wu, Weijie; Fang, Xiangjun; Chen, Hangjun; Han, Yanchao; Liu, Ruiling; Niu, Ben; Gao, Haiyan
Highlights: Bamboo shoot dietary fiber (BSDF-1) mitigates dextran sulfate sodium-induced colitis. BSDF-1 was characterized as a backbone consisting predominately of 1, 4-linked Glcp. BSDF-1 reduces pro-inflammatory cytokine production, intestinal barrier destruction. BSDF-1 regulates the intestinal microbiota composition. BSDF-1 has therapeutic potential for the prevention of inflammatory bowel disease. Abstract: A water-soluble dietary fiber named BSDF-1 (polysaccharide) was isolated from the bamboo ( Phyllostachys edulis ) shoot. BSDF-1was characterized as a backbone consisting predominately of 1, 4-linked Glcp, and the protective effects and mechanisms of the anti-inflammatory activity were investigated using a dextran sulfate sodium (DSS)-induced colitis mouse model. BSDF-1 administration significantly reduced colonic pathological damage, inhibited the activation of inflammatory signaling pathways, including nuclear factor-kappa B and NLR family pyrin domain containing 3 inflammasomes pathways. It restored the mRNA expression of tight junction proteins, including zonula occludens-1, claudin-1, and occludin. Furthermore, BSDF-1 treatment reduced Parabacteroides, Mucispirillum, Helicobacter, Bacteroides, and Streptococcus levels, whereas high-dose BSDF-1 treatment increased Prevotella, Alitipes, Anaerostipes, Odoribacter, Bifidobacterium, Butyricimonas, and Lactobacillus levels. In conclusion, BSDF-1 can inhibit the activation of inflammatory signaling pathways and restore the intestinal barrier function. Thus, BSDF-1 may be a valuable food supplement or nutraceutical to manage and prevent ulcerative colitis.